Reliability and Validity of the Persian Version of Dental Student Learning Education Questionnaire and a Researcher Made Questionnaire about In-terest of Dental Students in Their Field of Study - Faramarz Mojtahedzadeh; Esmaeil Yassini; Nafiseh Rahmani (Islamic Dental Association of Iran, 2015)
Background and Aim: Improving the quality of dental education significantly enhances the quality of services and promotes public health. The purpose of this study was to assess the reliability and validity of the Persian version of dental student learning education questionnaire (DSLES) and a researcher made questionnaire about interest of dental students in their field of study. Materials and Methods: A questionnaire composed of two major components was de-signed in this study. The first part, was a researcher made questionnaire related to stu-dents' interest in their field of study and the second part was the Persian translation of the DSLES. Delphi approach was used for content validation. Cronbach's Alpha and the Kappa coefficients were determined by SPSS for assessing reliability. Results: All indicators of content validity (except for 6 items in the second part) and the inter-rater agreement were higher than %75. The Cronbach's alpha for all subscales was higher than %75 and the Kappa for all items was higher than %73. According to the re-sults of 375 questionnaires, Cronbach's alpha for the first part was 79%, for the second part was 85% and for the entire questionnaire was 86%. Conclusion: The designed questionnaire can serve as an acceptable instrument in the Ira-nian educational settings.